2011
DOI: 10.1038/eye.2011.126
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological cure times in acanthamoeba keratitis

Abstract: Aims The purpose of this study was to estimate the duration of treatment necessary for sequential acanthamoeba laboratory tests from corneal scrapings to become negative, and to assess predictors that affect this duration period. Methods We included all patients with at least one positive acanthamoeba culture or Giemsa stain at the F.I. Proctor Foundation Microbiology Laboratory from 1996 to 2009. A parametric survival analysis was performed among patients with repeat cultures to assess significant predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…27 Similar to culture, PCR follow-up of corneal scraping could be tested to evaluate the clearance of the pathogen, even if detection of Acanthamoeba DNA could occur in the presence of dead microorganisms. Other AK diagnostic complementary tools, such as in vivo confocal microscopy, [28][29][30] could also be used to monitor treatment response, but this remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…27 Similar to culture, PCR follow-up of corneal scraping could be tested to evaluate the clearance of the pathogen, even if detection of Acanthamoeba DNA could occur in the presence of dead microorganisms. Other AK diagnostic complementary tools, such as in vivo confocal microscopy, [28][29][30] could also be used to monitor treatment response, but this remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in an online survey of worldwide ophthalmologists, Oldenburg et al found that PHMB and chlorhexidine were the most common choices as monotherapy for treating AK . Although the majority of patients achieve clinical cure, the duration of treatment for AK can be very long . and despite all the currently available drugs, many patients develop severe corneal scarring or even perforation…”
Section: Discussionmentioning
confidence: 99%
“…26 Although the majority of patients achieve clinical cure, the duration of treatment for AK can be very long. 27 and despite all the currently available drugs, many patients develop severe corneal scarring or even perforation. 28 The knowledge that ultraviolet radiation can be used to activate riboflavin and reduce pathogens in vitro and ex vivo such as in platelet concentrates, 12 together with the popularization of the CXL technique in which UVA is irradiated for 30 min at 3 mW/cm 2 (5.4 J) over a cornea treated with topical riboflavin, 29 led to the idea that the same parameters used for CXL could be used for reducing pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Treatment duration is generally lasting months. [ 2 ] Corneal hypoxia is a noninflammatory corneal complication caused by the extended contact lens wear and is characterized by corneal edema, infiltrative keratitis, and neovascularization. [ 3 ] It has been reported to recover several hours after removing contact lens.…”
Section: Introductionmentioning
confidence: 99%